The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1210/jcem-51-4-730
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadotropic Hypogonadism: Hormonal Responses to Low Dose Pulsatile Administration of Gonadotropin-Releasing Hormone*

Abstract: Patients with isolated gonadotropin deficiency were studied to determine whether pulsatile low dose gonadotropin-releasing hormone (GnRH) could induce the hormonal changes seen during normal puberty. Four male and two female patients with immature responses to a standard GnRH test (2.5 micrograms/kg) were given GnRH (0.025 micrograms/kg) iv every 2 h for 5 days. FSH responses varied between the sexes, and FSH concentrations in males rose continuously to 17.2 +/- 4.7 mIU/ml on day 5. In the females, FSH peaked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…In an effort to elucidate the nature of these changing responses we have previously administered low doses of GnRH in a pulsatile manner, to mimic the presumed physiological pattern of GnRH secretion, to female patients with absent or greatly reduced endogenous GnRH secretion. Our results (4,5) and those of others (6,7) have shown that the initial response to GnRH is one of predominant FSH secretion that later declines, while LH responses gradually increase. This pattern seen over 5 d of pulsatile GnRH injections is similar to that present during sexual maturation in girls.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In an effort to elucidate the nature of these changing responses we have previously administered low doses of GnRH in a pulsatile manner, to mimic the presumed physiological pattern of GnRH secretion, to female patients with absent or greatly reduced endogenous GnRH secretion. Our results (4,5) and those of others (6,7) have shown that the initial response to GnRH is one of predominant FSH secretion that later declines, while LH responses gradually increase. This pattern seen over 5 d of pulsatile GnRH injections is similar to that present during sexual maturation in girls.…”
Section: Introductionsupporting
confidence: 75%
“…Gonadotropin concentrations are reported as milliInternational Units of the second international reference preparation of human menopausal gonadotropin after conversion from LER 907, which was used as the assay standard. The limit of detectability of the estradiol assay depended upon the volume of plasma available and was 10-15 pg/ml when 2 ml were used, and 20-30 pg/ml when only 1 jections after which FSH rose to a mean of 5.3±0.3 on day 5. In both patients, plasma estradiol remained below assay detectability throughout the study.…”
Section: Introductionmentioning
confidence: 96%
“…The changing pattern in patients with a GnRH deficiency and delayed puberty shows that pulsatile GnRH is able to modify the pituitary response to GnRH within several days (8). Evidence for the idea that patients with a GnRH deficiency have a delayed response to GnRH compared with patients with delayed puberty as a result of impaired priming during the fetal and infant period was not found.…”
Section: Discussionmentioning
confidence: 92%
“…It has been suggested that intermittent delivery of GnRH to the pituitary gland is essential for gonadotrophin secretion to be maintained. Exogenous GnRH given in a pulsatile manner every 1\p=n-\2h to GnRH-deficient humans or monkeys can mimic the hormonal changes of puberty and the menstrual cycle Valk et al, 1980;Wildt et al, 1980). McLeod et al (1982a) have also reported that injections of low doses of GnRH every 2 h result in a sustained increase in pulsatile LH secretion in seasonally anoestrous ewes until the onset of a preovulatory LH surge, and that such animals, if primed with progesterone, will eventually ovulate and exhibit normal luteal function.…”
Section: Introductionmentioning
confidence: 99%